The redox of hydroxyl-assisted metallic filament induced resistive switching memory based on a biomaterial-constructed sustainable and environment-friendly device. (December 2018) - Zheng, L.; Sun, B.; Chen, Y.; Li, T.; Mao, S.; Zhu, S.; Wang, H.; Zhang, Y.; Lei, M.; Zhao, Y.
Abstract: Using biomaterial-constructed resistive switching memory devices has attracted great attention for the potential application in advanced electronic components because of their variety of advantages, such as low cost, sustainability, environment-friendly, and so on. In this work, after a series of treatments, an edible mushroom as an intermediate insulating material was assembled into an Ag/biofilm/metal structure, in which the metals such as Al, Cu, Ag, and Ti were chosen as the bottom electrode to explore in-depth physical mechanisms. The transmission mechanism of resistive switching memory behavior in an Ag/biofilm/metal device was studied in detail. It was found that the redox of hydroxyl-assisted Ag filaments could be easily formed on an inactive metal bottom electrode through the mushroom film by redox reaction under applied voltage. This work provides an ingenious potential application in wearable, flexible, sustainable, and environment-friendly biologically resistive random-access memories. Graphical abstract: Highlights: Four different bottom metal electrodes were assembled in our device. An organic resistive switching memory device based on mushrooms was prepared. This structure is environment-friendly, biodegradable, and continuable. This work indicates that the mushroom can be used as an electronic material.